STRATEGI PENGEMBANGAN PARIWISATA PACU JALUR MENUJU EVENT NASIONAL DI KABUPATEN KUANTAN SINGINGI - Wulandari, Fardhuni; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Kuantan Singingi Regency is one of the regencies that has excellent tourism, namely the well-known track runway culture. Pacu Jalur cultural tourism is a canoe race that is competed in the Kuantan River every year in order to commemorate the Birthday of the Republic of Indonesia. This study aims to determine how the pathway tourism development strategy towards the National event in Kuantan Singingi Regency. Then, to find out the inhibiting factors in tourism development, drive the path to the National event. The location of this research was conducted in Kuantan Singingi Regency, at the Department of Tourism and Culture of Kuantan Singingi Regency. Furthermore, data collection techniques are carried out by interviews, documentation and literature study. The result of this research is the tourism development strategy on the pathway to the national event in Kuantan Singingi Regency is still not optimal. this is caused by several factors such as lack of budget and human resources.Keywords: Strategy, Development, Pace Path